ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIK SISWA SMP PADA MATERI BILANGAN BULAT - Nurfauziah Nurfauziah; Luvy Sylviana Zanthy (Departement of Mathematics Education, 2019)
This study aims to see the extent to which junior high school students' mathematical problem solving abilities include understanding problems, planning strategies, solving problems and checking reliability. The subjects of this study were students of class VII B of Sumur Bandung Middle School, which amounted to 40 students. Data collection techniques use test techniques, while the techniques used to analyze data use percentage averages. The results showed that students' mathematical problem solving abilities were still low, seen from the percentage stating that students could not solve the problem and re-examine the problems given by the teacher. Based on the analysis that has been done, the results obtained are (1) students answer non-systematic questions, (2) lack of understanding of the sequence of problem solving, (3) students are too rushed to resolve the problem given. So the mathematical problem solving abilities of class VII B students at Sumur Bandung Middle School are in low qualifications.